Manipulation of solid-liquid interface of 4He by acoustic radiation pressure - Nomura, R.; Suzuki, Y.; Kimura, S.; Okuda, Y.; Burmistrov*, S. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2003)
Acoustic radiation pressure is thought to be very useful for solid 4He experiment under the microgravity. We observed that solid-liquid interface of 4He was manipulated by the acoustic wave. We applied the sound pulse perpendicularly to the flat interface between two transducers. The interface moved to the sound direction at low temperatures. We also checked how the interface moved when sound was applied parallel to the interface. Dynamics of the interface during andafter the sound pulse were recorded by a high speed CCD camera.